2017
DOI: 10.1242/dev.144477
|View full text |Cite
|
Sign up to set email alerts
|

The phosphatase Pgam5 antagonizes Wnt/β-Catenin signaling in embryonic anterior-posterior axis patterning

Abstract: The scaffold protein Dishevelled is a central intracellular component of Wnt signaling pathways. Various kinases have been described that regulate and modulate Wnt signaling through phosphorylation of Dishevelled. However, besides general protein phosphatases 1 and 2 (PP1 and PP2), no specific protein phosphatases have been identified. Here, we report on the identification and functional characterization of the protein phosphatase Pgam5 in vitro and in vivo in Xenopus. Pgam5 is a novel antagonist of Wnt/β-Cate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 88 publications
1
23
1
Order By: Relevance
“…Our previous study characterizes mitochondrial Pgam5 as repressor of the Wnt pathway by dephosphorylating Dvl ( Rauschenberger et al, 2017 ), whereas our data presented in this study suggest that cytosolic Pgam5 acts as an activator. This cellular localization–dependent dual role of Pgam5 in regulating Wnt/β-catenin signaling leads to the question of how mitochondrial Pgam5 specifically dephosphorylates Dvl but not β-catenin, whereas cytosolic Pgam5 is dedicated toward β-catenin dephosphorylation.…”
Section: Discussioncontrasting
confidence: 71%
See 1 more Smart Citation
“…Our previous study characterizes mitochondrial Pgam5 as repressor of the Wnt pathway by dephosphorylating Dvl ( Rauschenberger et al, 2017 ), whereas our data presented in this study suggest that cytosolic Pgam5 acts as an activator. This cellular localization–dependent dual role of Pgam5 in regulating Wnt/β-catenin signaling leads to the question of how mitochondrial Pgam5 specifically dephosphorylates Dvl but not β-catenin, whereas cytosolic Pgam5 is dedicated toward β-catenin dephosphorylation.…”
Section: Discussioncontrasting
confidence: 71%
“…Pgam5 is involved in regulating cell death pathways such as apoptosis and necroptosis as well as mitochondrial turnover by inducing mitophagy after mitochondrial damage ( Wang et al, 2012 ; Chen et al, 2014 ; Wu et al, 2014 ; He et al, 2017 ). It was recently shown that mitochondrial uncleaved Pgam5 can act as a negative regulator of Wnt/β-catenin signaling and that it dephosphorylates disheveled (Dvl), a positive regulator of Wnt signaling ( Rauschenberger et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…PGAM5 has been functionally linked to the regulation of mitochondrial dynamics, mitophagy, and cell death. It dephosphorylates various proteins localized at the outer membrane (OM) or in the cytosol (Takeda et al , ; Wang et al , ; Chen et al , ; Panda et al , ; Rauschenberger et al , ), suggesting that cleaved PGAM5 can be released from mitochondria. We recently identified in a proteomic survey the pro‐apoptotic protein Smac (DIABLO), the complex III surveillance factor TTC19 (Ghezzi et al , ; Bottani et al , ), the lipid transfer protein (LTP) STARD7 (Horibata & Sugimoto, ), and CLPB (Capo‐Chichi et al , ; Kanabus et al , ; Saunders et al , ; Wortmann et al , ) as additional substrates of PARL, highlighting the pleiotropic roles of PARL in mitochondria and its relevance for disease (Saita et al , ).…”
Section: Introductionmentioning
confidence: 99%
“…PGAM5 is a member of the phosphoglycerate mutase family, but exhibits protein phosphatase activity toward Ser/Thr (Takeda et al , ) and His (Panda et al , ). Recent studies highlighted the importance of PGAM5 in a variety of cellular processes, including mitochondrial dynamics (Wilkins et al , ; Lavie et al , ; O'Mealey et al , ), mitophagy (Chen et al , ; Wu et al , ; Hawk et al , ), programmed cell death (Wang et al , ; Lin et al , ; Zhuang et al , ; Xu et al , ; He et al , ), the WNT/β‐catenin pathway (Rauschenberger et al , ; Bernkopf et al , ), immune responses (Kang et al , ; Moriwaki et al , ), and longevity (Borch Jensen et al , ). Several lines of evidence suggest the close relationship of PGAM5 with Parkinson's disease.…”
Section: Introductionmentioning
confidence: 99%